2019
DOI: 10.2174/1381612825666190115144241
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Plectranthus-derived Diterpenes with Antitumoral Activities

Abstract: The study of natural sources such as plants, microorganisms and marine organisms has developed interest among the scientific community in recent years for their extensive and diverse chemical composition and consequent biological potential. The search for antitumor compounds is among the lead causes that justify phytochemical studies. Although some natural products have served as FDA approved chemotherapeutic agents, there is still a demand for the search of compounds with those characteristics. The Plectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The compound Diroy is the less bioactive abietane and this is in agreement with the more polar feature on the C-6 and C-7 positions. This polar structure-activity relationship could be explained due to a better membrane interaction [11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The compound Diroy is the less bioactive abietane and this is in agreement with the more polar feature on the C-6 and C-7 positions. This polar structure-activity relationship could be explained due to a better membrane interaction [11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies attribute these biological properties to the diterpenes expressed by this genus [8][9][10]. Our previous studies have demonstrated that the diterpenes isolated from Plectranthus genus induce apoptosis in various cancer cell lines, including human myeloid leukaemia, and pancreatic, lung, melanoma, prostate, and breast cancer [11][12][13][14][15][16][17]. The present study focuses on the properties of abietane diterpenes (Roy, Deroy, Diroy, and Parv D) isolated from P. madagascariensis and P. ecklonii.…”
mentioning
confidence: 96%
“…Most of the Plectranthus species are soft trailing semi-succulent to succulent herbs or shrubs and their stems, leaves, roots, and tubers are frequently used as traditional medicines for the treatment of various illnesses, including respiratory, digestive, and liver ailments [ 9 ]. Phytochemical studies on some species of Plectranthus revealed the presence of a large number of diterpenes and triterpenes [ 10 , 11 ]. Isolated terpenes from Plectranthus species are reported to possess antibacterial [ 12 , 13 , 14 ], antitumoral [ 15 , 16 , 17 , 18 ], antifungal [ 12 , 19 ], insecticidal [ 20 ], and antiplasmodial [ 20 ] activities.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the scientific literature concerning these species is scarce or even non-existent. P. hadiensis was earlier reported to have ethnopharmacological activity and to be a rich source of ent-abietane diterpenes [ 11 ]. This work aims to screen the antimicrobial, antioxidant, and cytotoxic properties of several Plectranthus spp.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the oxidation level of the abietane ring affects the antiproliferative selectivity of the compound. When compared to parviflorone D ( Salim et al, 2008 ), parviflorone F ( Srancikova et al, 2013 ) demonstrated higher cytotoxicity in Vero cell lines ( Garcia et al, 2019 ).…”
Section: Biological Activities Of Isolated Compounds From P Ecklonii Benthmentioning
confidence: 99%